A Review about various Problems of Disarmament - Kumar, Umesh (Universal Research Reports, 2017)
Disarmament is one of those phenomena of international politics which are regarded as solutions to international problems. There is an argument that armament race is causing war and hence war can be checked only by disarmament. Generally disarmament indicates the idea of limitation, control or reduction of armaments. Disarmament may also mean anything from a simple limitation to complete abolition of arms. Disarmament may be unilateral or multilateral, general or local, total or partial, controlled or uncontrolled.